Beyond the face: multidimensional care challenges and unmet needs in Hemifacial Microsomia families - Huang, Yan; Gui, Li (Frontiers in Public Health, 2025)
IntroductionHemifacial Microsomia (HFM), the second most common congenital facial deformity, significantly impacts patients’ physical appearance and psychosocial well-being, imposing considerable caregiving burdens on families. This study investigates the clinical characteristics of HFM patients, caregiver burdens, and unmet medical needs within Chinese online support communities.MethodsA cross-sectional study was conducted using convenience sampling of members from an HFM caregiver support group on WeChat APP. Data were collected via electronic questionnaires from March to April 2025, with 141 valid responses. The questionnaire assessed caregiver demographics, the child’s disease characteristics, prenatal history, and surgical experiences. For data analysis, we employed a multifaceted approach, utilizing descriptive statistics to summarize key variables, correlation analysis to explore relationships between factors, and thematic analysis to interpret responses to open-ended questions.ResultsThe study included 141 caregivers, mostly females (77.3%) aged 31–50 years (88.65%). Key findings revealed a higher prevalence of HFM in female patients (53.19%) and common comorbidities such as facial cleft (81.6%) and micrognathia (52.5%). Caregivers reported significant financial strain, with monthly household income and educational levels positively correlated with financial burden (p < 0.05). Rural residents and unemployed caregivers experienced heavier burdens (p < 0.05). Among 95 children with postoperative data, 21.88% expressed dissatisfaction with surgical outcomes, primarily due to unsatisfactory appearance. Additionally, 67.35% of families faced moderate-to-severe care burdens, with 85.11% of caregivers reported heightened sensitivity to social reactions toward their child’s condition.ConclusionHFM patients and their families face substantial medical, financial, and psychosocial burdens, including barriers to accessing care, meeting special needs, and receiving health education. Interventions addressing both clinical and emotional support are critical to improving their quality of life. Future research should employ diverse sampling methods and longitudinal studies to enhance the validity of findings on HFM caregiving experiences.